2009
DOI: 10.1136/bjsm.2009.068759
|View full text |Cite
|
Sign up to set email alerts
|

Injuries among male and female World Cup alpine skiers

Abstract: Background: Limited knowledge exists on injuries among professional alpine skiers. Objective: To describe the risk of injury and the injury pattern among competitive World Cup alpine skiers during the competitive season. Methods: Retrospective interviews were performed with all World Cup athletes from 10 nations at the end of the 2006-7 and 2007-8 winter seasons, and all acute injuries occurring during the 4.5-month competitive season were recorded. If the athlete was not present, their coaches or medical pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
266
13
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(304 citation statements)
references
References 31 publications
22
266
13
3
Order By: Relevance
“…Knee injuries, especially ruptures of the anterior cruciate ligament (ACL), represent a significant problem in professional alpine skiing (Flørenes et al, 2009) as illustrated by the case of a 21-year-old skier. At 16 years the skier ruptured his left anterior cruciate ligament, medial collateral ligament and the medial meniscus.…”
Section: Alpine Skiingmentioning
confidence: 99%
“…Knee injuries, especially ruptures of the anterior cruciate ligament (ACL), represent a significant problem in professional alpine skiing (Flørenes et al, 2009) as illustrated by the case of a 21-year-old skier. At 16 years the skier ruptured his left anterior cruciate ligament, medial collateral ligament and the medial meniscus.…”
Section: Alpine Skiingmentioning
confidence: 99%
“…Unfortunately, there is very little data on injury prevention programs in ski racing so far and to our knowledge. However, statistical evidence has been proven for only five of the risk factors, and only one prevention measure has been demonstrated to significantly reduce injury risk: Insufficient core strength [17], female sex [5,[17][18][19], high skill level' [16]; 'unfavorable genetic predisposition' [22]; and the combination of highly shaped, short, and wide skis [8]. To date, only the combination of less-shaped and longer skis with reduced profile width was statistically confirmed to have a positive effect on ACL-injury risk in alpine ski racing [8].…”
Section: Discussionmentioning
confidence: 99%
“…Flørenes et al found that the injury rates in the FIS World Cup during 2006-2008 were found to be 36.7 per 100 athletes [3]. All the studies conducted on ski racing, reported that the knee joint was the most commonly injured body part with a high number of ACL injuries, accounting for 28%-36% of all injuries [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Westin et al [15] demonstrated that almost 50% of all the skiers during their four year academic period were afflicted by one or more severe injuries. In another study interviewing 2121 world cup skiers and snowborders, 705 injuries were recorded [14]. One severe injury can end a skier's athletic career, so studying different aspects of this phenomenon seems to be very important in order to prevent alpine ski injuries.…”
Section: Introductionmentioning
confidence: 99%
“…For one athlete an injury can be seen as a failure and for another athlete as liberation. Because of the high risk of injury in competitive alpine skiing [14,15], it is important that the coaches work with their skiers to develop strategies that help the athletes to manage skiing without getting injured.…”
Section: Introductionmentioning
confidence: 99%